Reflections on India’s 2018 Guidelines on Cross Border Electricity Trading Vis-a-vis SAARC versus ASEAN - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2019)
Despite the 2014 Indo-Nepal Electric Power Trade Agreement and the 2014 SAARC Framework Agreement for Energy Cooperation (Electricity), India issued two Guidelines within two years, one in 2016 and the other in 2018. After discussing the genesis of these two Guidelines, the author attempts to analyze the 2018 Guidelines. With India citing electricity trade as “issues of strategic, national and economic importance”, that was couched into “issues of international relations” in the 2018 Guidelines, this explains why the SAARC Framework Agreement for Energy Cooperation (Electricity) has made no headway at all in the last four years. The SAARC region, home of Buddha, Ashok, Akbar etc. may, perhaps, have to look east to the ASEAN on how electricity trading is done there. Electricity, besides being a strategic tool, is also an economic tool that should be used to uplift the quality of life of hundreds of millions of South Asians mired in deep poverty. Unless India takes the initiative akin to ASEAN, SAARC citizens will continue to wallow in that poverty!